Gold Pawn Analysis On Islamic Banking Gold Partner Products Maslahah In Bank Jabar Banten Sharia Indramayu Branch Office - Khoirul Izzah (Penerbit Hellow Pustaka, 2023)
The contract used for gold pawning on gold partner products IB maslahah at Bank Jabar Banten Syariah Indramayu Sub-Branch Office uses a multi-contract which is structured in qard contracts, rahn contracts and ijarah contracts. Adhering to the DSN fatwa No.26/DSN-MUI/III/2002 and the Civil Code (KUHPerdata) articles 1150-1160 and to the ijarah contract which functions as an ujrah (fee), where the customer agrees to the DSN fatwa No. 09/DSN-MUI/IV/2000 giving ujrah to banks for bank services in storing and maintaining customer gold . The view of muamalah fiqh in the implementation of gold pawning on gold partner products IB maslahah at Bank Jabar Banten Syariah Indramayu Sub-Branch Office regarding the contract is the gold pawning contract used in Islamic banking, especially at Bank Jabar Banten Syariah has 3 (three) contracts, namely, qard contract (cooperation contract), rahn (pawn) contract and ijarah contract (leasing), the three contracts are used in one transactions or what we call multi-contracts ( hybrit contracts). Multi-contract activities in the Islamic economy itself have opinion Which different with activity multi-contract Alone. In classical muamalah fiqh pawning gold which has an element of merging contracts between buying and selling and leasing is strictly prohibited, due to fear of elements of usury. However, contemporary muamalah fiqh expert Erwandi Tarmizi allows the existence of multiple rahn and qard contracts. in which there is an ijarah contract with conditions, Islamic banks must provide two choices to customers.